2006
DOI: 10.1007/s10745-006-9095-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Invasive Alien Species on Rural Livelihoods: Case Examples and a Framework from South Africa

Abstract: The detrimental impacts of invasive alien species (IAS) on ecosystem goods and services and local and regional economies are well documented. However, the use of IAS by rural communities is little understood, and rarely factored into IAS control programmes. Understanding the use of IAS by rural communities and factoring these into cost-benefit models is complex, depending upon a range of local-level attributes such as the time since invasion, abundance, and local-level costs and benefits. This paper reports on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
232
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(244 citation statements)
references
References 21 publications
6
232
0
6
Order By: Relevance
“…One framework suggests that the abundance of invasions is the dominant factor influencing perceptions (Shackleton et al 2007). Other factors such as biophysical characteristics of the local environment, potential uses, growth form of the plant, mode of introduction, social context of the area (socioeconomic status, local policies, and land tenure), and familiarity with the invasive species clearly also shape perceptions and use of invasive aliens (Kull et al 2011;Rai and Scarborough 2014).…”
Section: Factors Shaping Knowledge Perceptions and Practices Of Promentioning
confidence: 99%
See 4 more Smart Citations
“…One framework suggests that the abundance of invasions is the dominant factor influencing perceptions (Shackleton et al 2007). Other factors such as biophysical characteristics of the local environment, potential uses, growth form of the plant, mode of introduction, social context of the area (socioeconomic status, local policies, and land tenure), and familiarity with the invasive species clearly also shape perceptions and use of invasive aliens (Kull et al 2011;Rai and Scarborough 2014).…”
Section: Factors Shaping Knowledge Perceptions and Practices Of Promentioning
confidence: 99%
“…This is in agreement with other sources that have shown that Prosopis invasions in the Northern Cape province increased from approximately 128 000 ha in 1974 to 1.5 million ha in 2007, and that the extent increased by around 8 % per annum from 1974 to 2007 (Van den Berg 2010; van Wilgen et al 2012). This will increase costs and reduce benefits, thereby increasing human vulnerability in the future (Shackleton et al 2007;Wise et al 2012). Most people (98 %) would like to see Prosopis populations reduced in the study area (Table 5).…”
Section: Knowledge Perceptions and Practices Relating To Prosopis Imentioning
confidence: 99%
See 3 more Smart Citations